Minimally invasive Oxford medial unicompartmental knee arthroplasty in young patients - Streit, Marcus R.; Streit, Julia; Walker, Tilman; Bruckner, Thomas; Kretzer, Jan Philippe; Ewerbeck, Volker; Merle, Christian; Gotterbarm, Tobias (Knee surgery, sports traumatology, arthroscopy, 2017)
Purpose Advanced knee arthritis in young patients is a challenging problem that may necessitate surgical treatment. There are few published studies of mobile-bearing unicompartmental knee arthroplasty (UKA) in young patients, while indications have expanded to its use in this demanding patient group.MethodsThe clinical and radiographic results of the first 118 consecutive Oxford medial UKAs (OUKA) using a minimally invasive technique (phase 3) in 101 patients 60 years of age or younger at the time of surgery were evaluated. Median age at surgery was 57 (25-60) years. Kaplan-Meier survivorship analysis was used to estimate implant survival.ResultsMean time of follow-up evaluation was five (SD 1.6) years. At final follow-up, three patients (three knees) had died, and two patients (three knees) were lost to follow-up. Five knees were revised: three for unexplained pain, one for early infection and one for bearing fracture. There was one impending revision for progression of osteoarthritis in the lateral compartment. The radiographic review demonstrated that 5 % of the knees had progressive arthritis in the lateral knee compartment, of those 2 % with full joint space loss and pain. The Kaplan-Meier survival analysis, using revision for any reason as the endpoint, estimated the five-year survival rate at 97 % (95 % CI 91-99). Ninety-six per cent of the non-revised patients were satisfied with the outcome, and 4 % were dissatisfied. The mean Oxford knee score was 41 (SD 7), with 6 % of the knees having a poor result. The mean AKSS was 89 (SD 14), mean flexion was 129° (SD 13) and the mean UCLA score was 6.8 (SD 1.5).ConclusionMinimally invasive Oxford medial UKA was reliable and effective in this young and active patient cohort providing high patient satisfaction at mid-term follow-up. Progressive arthritis in the lateral knee compartment was a relevant failure mode in this age group. Most revisions were performed for unexplained pain, while we did not find loosening or wear in any patient.Level of evidenceIV.
Published online: 10 May 2015
Gesehen am 07.04.2017